Carer‐reported measures for a dementia registry: A systematic scoping review and a qualitative study. (16th November 2022) - Lin, Xiaoping; Ward, Stephanie A.; Pritchard, Elizabeth; Ahern, Susannah; Gardam, Madeleine; Brodaty, Henry; Ryan, Joanne; McNeil, John; Tsindos, Tess; Wallis, Kasey; Jeon, Yun‐Hee; Robinson, Sandra; et al.
Abstract: Objectives: Informal carers play a critical role in supporting people with dementia. We conducted a scoping review and a qualitative study to inform the identification and development of carer‐reported measures for a dementia clinical quality registry. Methods: Phase 1—Scoping review: Searches to identify carer‐reported health and well‐being measures were conducted in three databases (MEDLINE, PsycINFO and Embase). Data were extracted to record how the measures were administered, the domains of quality‐of‐life addressed and whether they had been used in a registry context. Phase 2—Qualitative study: Four focus groups were conducted with carers to examine the acceptability of selected measures and to identify outcomes that were important but missing from these measures. Results: Phase 1: Ninety‐nine carer measures were identified with the top four being the Zarit Burden Interview ( n = 39), the Short‐Form12/36 ( n = 14), the Brief Coping Orientation to Problems Experienced scale and the Sense of Coherence scale (both n = 9). Modes of administration included face‐to‐face ( n = 50), postal ( n = 11), telephone ( n = 8) and online ( n = 5). No measure had been used in a registry context. Phase 2: Carers preferred brief measures that included both outcome and experience questions, reflected changes in carers' circumstances and included open‐ended questions. Conclusions: Carer‐reported measures for a dementia clinical quality registry need to include both outcome and experience questions to capture carers' perceptions of the process and outcomes of care and services. Existing carer‐reported measures have not been used in a dementia registry context and adaption and further research are required.